Pengaruh Karakteristik Organisasi Dan Budaya Organisasi Terhadap Komitmen Manajerial, Kepercayaan Anggota dan Partisipasi Anggota Serta Dampaknya Pada Kinerja Koperasi Pada Koperasi Kredit (Credit Union) di Flores - Hyronimus Se (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2020)
This study aims to analyze the influence of organizational characteristics and organizational culture on managerial commitment, member trust, and member participation, the impact on the performance of cooperatives in credit unions in Flores, East Nusa Tenggara Province, Indonesia. The population in this study included administrators, supervisors, and managers of all credit unions in Flores. The total sample of 237respondents was obtained by using the simple random sampling technique. Data analysis techniques usingStructural Equation Model (SEM) with concepts and applications using Analysis of Moment Strucues (AMOS) program version 21. The results of the study show that: (1) organizational characteristics significantly influence managerial commitment and member participation, (2) organizational culture has a significantly effect on managerial commitment, member trust, and member participation, (3) managerial commitment has a significantly effect on cooperative performance, (4) member trust has a significantly effect on cooperative performance, (5) member participation has a significantly effect on performance cooperative.